The Legal Structure's Impact on Crime Reduction: Challenges and Opportunities - M D, Sintong Hamonangan; Panggabean, Mompang Lycurgus; Siregar, Rospita Adelina (TATOHI: Jurnal Ilmu Hukum, 2026)
Introduction: This paper analyzes the strategic role of legal structure in addressing crime as a social phenomenon that threatens public order and legal stability. Legal structure comprises legal norms and law enforcement institutions, including the police, prosecutors, courts, and correctional facilities, which collectively support crime prevention, law enforcement, and offender rehabilitation.Purposes of the Research: The research aims to examine the functions of legal structure in preventing, suppressing, and rehabilitating criminal conduct, as well as to identify institutional and societal challenges affecting the effectiveness of crime control.Methods of the Research: This study applies a normative juridical approach, using statutory and conceptual analysis to assess criminal law policies and the performance of the criminal justice system in crime prevention and control.Findings of the Research: The findings reveal that legal structure operates through three key stages: legislative formulation grounded in legality, proportionality, and humanism; judicial application requiring institutional coordination within the criminal justice system; and administrative execution focused on offender rehabilitation and reintegration. The study identifies internal obstacles such as corruption, limited institutional capacity, regulatory complexity, and bureaucratic inefficiency, alongside external challenges including low public legal awareness, unequal access to justice, and rapid technological change. The research proposes reforms to strengthen institutional integrity, enhance legal capacity and infrastructure, harmonize regulations, expand legal education and free legal aid, and promote restorative justice involving community participation. The originality of this study lies in its integrated, stage-based analysis of legal structure and its emphasis on institutional synergy and public engagement as essential elements for sustainable crime prevention and substantive justice.